(untitled) (KYAMC Journal, 2024)
Foreign bodies (FBs) in the colon, rectum and anal canal are not unusual. Colorectal Foreign Bodies (CRFBs), whether administered per-anally or swallowed orally, intentionally or unintentionally, bring management challenges to the attending physicians and surgeons. CRFBs are usually seen in the adult patients with perverted sexual or erotic or psychosis, or mental retardation, or in drug smugglers or prisoners, and anorectal FBs (ARFBs) are sometimes seen on accidental or careless swallowing with or without food, or per-anal administration in all age groups. Careless elderly patients with or without visual problems, with or without using artificial dentures are also not unusual victims. Self-administration per-anally to attempt relief from constipation has also been described, especially in adults and elderly people. Many of these FBs can pass with intestinal contents and may be thus removed with stool without complications. The sharp FBs can penetrate the bowel wall leading to serious consequences, and a relatively large FB can get impacted causing bowel obstruction. The presentation may be straightforward and sometimes may be exquisitely concealing. The objective of this review article is to understand and share the management strategies which would be very much helpful to all concerned. KYAMC Journal Volume: 14, No: 04, January 2024: 240-245.